Developing an integrated framework for analyzing customer complaint flow with Six Sigma - Ajaya Kumar, Aravind Vasudevaru (My University, 2023)
The abstract of the thesis involves a structured development following the Six Sigma Methodologies incorporated into the analyzing and development of customer complaint process collection in Mölnlycke Health Care. Eventhough, previous research have been done regarding similar acumen, in this particular thesis, a special focus has been given to link the KPI of the organisation to that of the detailed collection of the complaint system identifying the pitfalls in the process, thereby helping to produce substantial results in the organisation level dynamics and decision making.
Keywords: Six Sigma; Manufacturing; Customer Complaint resolution